2013
DOI: 10.4172/2329-9002.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characterization and Mine Soil Genesis in Age Series Coal Mine Overburden Spoil in Chronosequence in a Dry Tropical Environment

Abstract: A pre-requisite to any revegetation plan, as well as restoration of degraded land is the knowledge of physicochemical characterization, which is crucial for prediction of ecological succession for mine overburden spoil, including soil texture, hydrological regimes, pH, organic carbon, nitrogen and extractable phosphorous. Effects of mining activities are markedly adverse, because many of the beneficial soil characteristics may require a long span of time to develop through pedogenic processes, in order to reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…In this study, the acidity of the spoil soil decreased significantly with the increase in spoil soil age indicating the reduction in AMD due stabilization of sulfide minerals or due to the passive reclamation. Similar results were also reported from spoil soils of Raniganj coal fields [31] and Basundhara colliery [7] in India. Due to rugged hilly terrain with different levels of elevation in the study sites, the exposed acids might have leached down leading to the spatial and temporal decrease in acidity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In this study, the acidity of the spoil soil decreased significantly with the increase in spoil soil age indicating the reduction in AMD due stabilization of sulfide minerals or due to the passive reclamation. Similar results were also reported from spoil soils of Raniganj coal fields [31] and Basundhara colliery [7] in India. Due to rugged hilly terrain with different levels of elevation in the study sites, the exposed acids might have leached down leading to the spatial and temporal decrease in acidity.…”
Section: Discussionsupporting
confidence: 89%
“…The correlation analysis revealed that a decrease in acidity increased the availability of N and P which in turn helped in the growth of plants, and soil microorganisms. Maharana and Patel [7] also found low N and P in the spoil soils as compared to undisturbed forest soil. Phosphate is an anion and forms strong bonds with particles that generate anion exchange capacity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Mined land reclamation studies across the world have found that within about a decade following placement, mine soils begin to develop genetic horizons and accumulate organic carbon (Ciolkosz et al 1985;Haering et al 2004;Maharana and Patel 2013). Plant growth media used in mine reclamation may include topsoil and/or overburden (e.g., surface and subsurface materials) given that physical, chemical, and mineralogical properties are deemed suitable (Angel 1973;Daniels and Amos 1985;Hons 1978).…”
Section: Introductionmentioning
confidence: 99%